Pharmacokinetics, Pharmacodynamics, Safety, Tolerability, and Immunogenicity of the QX002N anti-IL-17 Monoclonal Antibody: A Phase I, Randomized, Double-Blind, Single Ascending Dose Study in Healthy Chinese Volunteers - Wu, Min; Zhang, Hong; Li, Qianqian; Chen, Hong; Fang, Min; Yang, Lizhi; Ding, Yanhua (Frontiers in Pharmacology, 2022)
Background: The innovative injection of interleukin 17 A (IL-17A) monoclonal antibody QX002N is being developed to treat active ankylosing spondylitis and plaque psoriasis in adults. Objective: This study investigated the PKs, PDs, safety, tolerability, and immunogenicity of single ascending subcutaneous injections of QX002N in healthy Chinese volunteers. Methods: A total of 65 healthy subjects were enrolled in a randomized, double-blind, placebo-controlled, single ascending dose phase I study (10–320 mg). Ten subjects were allocated to each cohort (containing 8 subjects treated with QX002N and 2 with placebo), except cohort 1 (only 4 subjects treated with QX002N and 1 with placebo). The studies on pharmacokinetics (PK), pharmacodynamics, tolerability, and immunogenicity of QX002N were performed. Results: Our study showed that QX002N injection was well tolerated, without deaths, serious adverse events, or discontinuations due to treatment-emergent adverse events (TEAEs). Neither more frequency nor high severity of the drug-related adverse reaction was observed with increasing QX002N dose. The TEAEs in all subjects were considered Grades 1–2 (CTCAE 5.0) except for one case of Grade 3 (hypertriglyceridemia). Tmax of QX002N was obtained from 168–240 hours across the dose range after administration. The Cmax and area under the curve (AUC) of QX002N increased in proportion to dose, and showed linear PKs. Anti-drug antibody positivity was detected in one (1.9%) subject after drug administration. Conclusions: QX002N was well tolerated in our study. Based on the PKs and safety results of QX002N, 80 mg is recommended as the effective dose for a future phase Ib study. The registration number of our study is ChiCTR1900023040 (http://www.chinadrugtrials. org.cn/).